Model of Curriculum Development of Islamic Religious Education in Elementary Schools - Muda, Fat Fadilah Ismi K.; Yahiji, Kasim; Ondeng, Syarifuddin; Arif, Muh. (Newinera Publisher, 2023)
This article is a literature review research. With the title Model of Islamic Religious Education Curriculum Development in Elementary Schools, the data collection technique used in this study is through related journals and books. The data analysis used is content analysis. The data collection technique used is to look for data related to things or variables in the form of notes, books, essays or articles, magazines, and collect library data or research objects obtained from scientific journals and electronic searches covering two Google Schoolar issues 2015-2023. Islamic Religious Education is an effort to nurture and nurture students so that they can always understand the teachings of Islam as a whole, live the goals, and ultimately be able to practice and make Islam a view of life. The curriculum has an impact on the development of the times so that the curriculum must always be developed in order to adjust.